1997
DOI: 10.1093/protein/10.3.231
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of thermal stability of Streptomyces cholesterol oxidase by random mutagenesis and a structural interpretation

Abstract: Random mutagenesis was used to enhance the thermal stability of Streptomyces cholesterol oxidase. Four thermostable mutants were isolated and the following amino acid substitutions were identified: Ser103 to Thr (mutant S103T), Val121 to Ala (mutant V121A), Arg135 to His (mutant R135H) and Val145 to Glu (mutant V145E). The wild-type and mutant enzymes were purified and characterized. The properties of mutants S103T, V121A and R135H were similar to those of the wild type but they showed improved thermal stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 1 publication
2
36
0
Order By: Relevance
“…To identify the amino acid residues in ChoA b that are pertinent to its thermostability, three amino acid residues were selected to be mutated: Q153E, F128L, and S143H. Among the resulting mutant enzymes, E145 and H135 (in ChoA b , i.e., Q153 and S143) had improved thermostability compared with the wild-type enzyme in ChoA S (Nishiya et al 1997). Furthermore, the mutant enzyme L119F (in ChoA b , i.e., F128) was more unstable than the wild-type enzyme (Murooka Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To identify the amino acid residues in ChoA b that are pertinent to its thermostability, three amino acid residues were selected to be mutated: Q153E, F128L, and S143H. Among the resulting mutant enzymes, E145 and H135 (in ChoA b , i.e., Q153 and S143) had improved thermostability compared with the wild-type enzyme in ChoA S (Nishiya et al 1997). Furthermore, the mutant enzyme L119F (in ChoA b , i.e., F128) was more unstable than the wild-type enzyme (Murooka Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For crude or purified CHOx, the activity determination assay method based on the same principle is used. In this method when In another assay, Nishiya et al [29] have reported the use of cholesterol oxidase indicator plate for screening of CHOx producing colonies. These plates are prepared by adding cholesterol, Triton X-100, o-dianisidine and peroxidase to the agar medium.…”
Section: Analysis Of Cholesterol Oxidase Activitymentioning
confidence: 99%
“…The indicator plates were prepared by adding 1 g cholesterol, 1 g Triton X-100, 0.1 g o-dianisidine and 1000 U horseradish peroxidase to 1 l of LB agar (pH 8.0) and 0.1 ml of 10 4 c.f.u. ml -1 culture was then spread on each plate and incubated at 30°C for 48 h (Nishiya et al 1997). This produces an intense brown azo compound when cholesterol activity is present.…”
Section: Cholesterol Oxidase Indicator Platesmentioning
confidence: 99%